Practices on the Periphery: Highly Educated Chinese Immigrant Women Making Occupational Niches in Canada - Hongxia Shan (Adult Education Research Conference, 2007)
I examine learning as part of the process where immigrants negotiate personal and profession identities and participate in the Canadian labour market. I argue for a mutually-constitutive relationship between individual practices, identity construction and Canadian workplace accessibility and receptivity underpinned by gender, race and class relations and perceived language differences.